Registers in Oral Speech of Mowindahako: Metafunctions and The Way of Life of The Tolakinese - Pehala, Ilfan Askul; Zur, Sarjaniah (Universitas Negeri Makassar, 2023)
Abstract. This research is oriented toward the role of registers in mowindahako custom. This qualitative research is focused on the lexis and speech of mowindahako from a Sociolinguistics perspective. The data collected and carried out through direct observations during customs be held and interviews with the participants in open-ended question perspective. The data were analyzed using BUL/Sharing Elements technique, coding according to the research object variables and thematic analysis, and ethnoscience analysis. The results showed that its register is divided into 2 types of expression, both are verbal expression in high formalistic poetic diglossia (wua-wua ndulura) and non-lingual (non-verbal: the things, body movements of participants in the mombesara process, and 4 traditional participants). Register used acts as a code or signal for the participants in the interaction process. This is an abstract and concrete realization of metafunction whose discourse provides an understanding of the purpose and meaning of mowindahako which has a philosophical function. This function is seen through the ideational, participants' ideational, logical, and experiential concepts al concept is based on the discourse in the mombesara process and the interpersonal traditional participants. Mowindahako's register construction ultimately showed the world what Tolakinese society is and how they are by through complex verbal and non-verbal metafunctions and stratification, axiological cognition, and their mindset and outlook on life. Keywords: Register, Diglossia, Metafunctions, Mowindahako, Mombesara